Green signals of new ventures: investigating the impact of environmental orientation on funding and the moderating role of lead venture capitalists - Patrick-Peter Herold; Franziska Schlichte; Sebastian Junge (Small Business Economics, 2025)
Drawing on signaling theory, this study investigates whether the environmental orientation of new ventures serves as an important signal related to funding outcomes. Analyzing a dataset of 2003 funding rounds completed in the U.S. during 2022, our findings reveal that the environmental orientation of a new venture positively influences pre-IPO funding outcomes. Furthermore, this effect is positively moderated by the prominence of lead venture capital investors. Our post hoc analysis offers a valuable temporal perspective and suggests that our findings generalize across both early-stage and late-stage funding rounds, but not seed funding. This study contributes to the literature on financial resource acquisition and signaling theory, and also offers valuable implications for practitioners, helping them navigate the competitive funding environment more effectively.
Keywords: L26; G24; M13; Q56; 330; Entrepreneurs; Funding; New ventures